La subsanación del derecho de la edificación, como requisito previo para interponer la acción reivindicatoria - Martínez Floriano, Oscar (2016)
Today to bring the action claiming the doctrine requires a series of requirements such as: a) the claimant is the owner of the property, b) the defendant is in possession of the property, c) that the good is identifiable and can It is individualized. That's why today when the action for repossession found lots of supreme executory that do not meet evenly , about the alleged stands where the applicant owns the land but not the construction of bad faith; so that in this case, the supreme meeting resolved to declare inadmissible the request for claim , however this approach is not uniform in the supreme court , as it was also ruled on that when the owner of demand land claim and can not prove the ownership of the building in which it is declared by accession demand founded claim. The aim of this research is to determine that by demanding action claiming ownership of land where he has built a third, the same can not prove the ownership of the buildings in bad faith, the applicant must operate primarily seeks to claim the ground and as ancillary to the accession of the building in bad faith. Also after analyzing the doctrine and jurisprudence in this paper is to show that it is not possible to petition the restitution of land and building by action claiming, if only has accredited the right to the land, so to being one of the attributes of the property under Article 923 of the Civil Code, it can only be exercised is credited what is proper. That is why we address this problem we consider that at the time of filing the claim must petition as principal claim claim the land and as ancillary to the building in bad faith, then to obtain a favorable ruling, the plaintiff may regularize Factory or building with the competent Municipality, through the regularization process established by Law 29090 and its Regulations supreme decree 024-2008 - house